PENERAPAN BREADTH FIRST SEARCH UNTUK MENGELOLA KEUANGAAN DENGAN MENENTUKAN KARAKTERISTIK INVESTASI INDIVIDU - Chandra, Danil; Ramaningtyas, Amalia Tri; Hakim, Lukman (Jurnal Teknik Informatika UNIKA Santo Thomas, 2021)
Investment is an activity to manage finances to achieve their financial dreams. Investing has its own challenges for each individual. In general, people are very hesitant to invest for fear of loss or usury. One way to avoid losses from investing is to know the characteristics of self-investment. In this study, a website-based application was designed to identify the investment character. To recognize the characteristics of research data needed as application knowledge to make decisions. Breadth First Search (BFS) can search for characters that match the knowledge data that has been planted. Through this research, it can be seen that BFS has a sufficient level in recognizing and classifying characters. The accuracy rate of BFS in recognizing characteristics and providing related explanations obtained from the test is 91.6%